The essential diabetes Instant Pot cookbook : healthy, foolproof recipes for your electric pressure cooker - Morante, Coco (Ten Speed Press, 2020)
"A collection of 75 simple, tasty recipes for diabetics and prediabetics that make eating balanced meals a snap with the incredibly popular electric pressure cooker, the Instant Pot. When cookbook author Coco Morante and her husband were both diagnosed with insulin-related conditions, they struggled to incorporate balanced meals into their busy schedules. So Coco decided to use the Instant Pot's convenience to make eating healthful, nutrient-dense dishes easy. The result? This enticing collection of 70 recipes for breakfast, lunch, dinner, and dessert that proves you don't have to sacrifice flavor to eat well. Featuring hearty, filling dishes like Whole Grain Apple Cinnamon Strata, Smoky Deviled Eggs, and Lamb and Sweet Potato Shepherd's Pie, this cookbook is a life saver for the more than 100 million adults with diabetes in this country, along with those who have prediabetes, PCOS, and other conditions involving insulin resistance. And best of all, every recipe is authorized by Instant Pot and approved by endocrinologist and foreword-writer Dr. Jessica Castle. With beautiful photography and an attractive package, this book is essential for home cooks who want to take back their health"--